Dimorphic Leaf Development of the Aquatic Plant Callitriche palustris L. Through Differential Cell Division and Expansion - Koga, Hiroyuki; Doll, Yuki; Hashimoto, Kei; Toyooka, Kiminori; Tsukaya, Hirokazu (Frontiers in Plant Science, 2020)
Heterophylly, or phenotypic plasticity in leaf form, is a remarkable feature of amphibious plants. When the shoots of these plants grow underwater, they often develop surprisingly different leaves from those that emerge in air. Among aquatic plants, it is typical for two or more distinct leaf development processes to be observed in the same individual exposed to different environments. Here, we analyze the developmental processes of heterophylly in the amphibious plant Callitriche palustris L. (Plantaginaceae). First, we reliably cultured this species under laboratory conditions and established a laboratory strain. Then we established a framework for molecular-based developmental analyses, such as whole-mount in situ hybridization. We observed several developmental features of aerial and submerged leaves, including changes in form, stomata and vein formation, and transition of the meristematic zone. Then we defined developmental stages for C. palustris leaves. We found that in early stages, aerial and submerged leaf primordia had similar forms, but became discriminable through cell divisions with differential direction, and later became highly distinct via extensive cell elongation in submerged leaf primordia.